A comperative study between Malaysia and United Kingdom (UK) on the protection for pregnant employee from unfair dismissal / Rose Syahirah Rosdin and Nur Hazirah Husziabidi. - Rosdin, Rose Syahirah; Husziabidi, Nur Hazirah (2013)
This research paper is regarding the unlawful dismissal of pregnant woman on the grounds of pregnancy. This research is a comparative where we choose to compare between laws in Malaysia and United Kingdom on the unlawful dismissal. The reason of why we choose United Kingdom because United Kingdom has a similar jurisdiction with Malaysia. The term used for these two countries regarding our topic is a bit different. United Kingdom uses the term 'unfair dismissal' while Malaysia uses the term 'unlawful dismissal'. Both of these terms carry the same meaning and it will be used interchangeably. Another term that will be used interchangeably in this research is the term 'worker' and 'employee'. The law that governs this issue is different in both countries. In United Kingdom, their laws cover all aspect of pregnancy which is during their pregnancy phase till the end of maternity leave. However for Malaysia, the laws only cover protection from unlawful dismissal during the maternity leave. Some of the deciding cases will also be examined to see the application of these laws to the real situation that is happening. This research will also examine the possible application of the protection laws in United Kingdom in Malaysia.